2006
DOI: 10.1159/000094244
|View full text |Cite
|
Sign up to set email alerts
|

Amantadine Resistance among Porcine H1N1, H1N2, and H3N2 Influenza A Viruses Isolated in Germany between 1981 and 2001

Abstract: This study was designed to gain insight into amantadine susceptibility of porcine influenza A viruses isolated in Germany between 1981 and 2001. The 12 studied H1N1, H1N2, and H3N2 porcine influenza virus strains were isolated in chicken eggs and passaged once in MDCK cells. Plaque reduction assays were applied to examine virus susceptibility to amantadine. Genotyping was used to confirm drug resistance. In the results of these antiviral studies, only 3 of the 12 isolates were shown to be amantadine-susceptibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 45 publications
2
33
1
Order By: Relevance
“…The influenza viruses of various hosts acquired the mutation at position 31 independently and almost simultaneously. Schmidtke et al reported the emergence of amantadine-resistant strains of swine influenza virus in the 1980s and suggested that this might have been caused by a reassortment event and that further reassortment between these swine and human influenza viruses could cause an increase in the amantadineresistant M gene in human influenza virus (32). Our results are contrary to this suggestion.…”
Section: Discussioncontrasting
confidence: 99%
“…The influenza viruses of various hosts acquired the mutation at position 31 independently and almost simultaneously. Schmidtke et al reported the emergence of amantadine-resistant strains of swine influenza virus in the 1980s and suggested that this might have been caused by a reassortment event and that further reassortment between these swine and human influenza viruses could cause an increase in the amantadineresistant M gene in human influenza virus (32). Our results are contrary to this suggestion.…”
Section: Discussioncontrasting
confidence: 99%
“…The NMR structure of the complex of M2WJ332 with the channel was solved for a peptide spanning from 19 to 49, which includes the TM and portions of the cytoplasmic domain and ectodomain. Two-dimensional 15 N heteronuclear single quantum coherence (HSQC) spectra for this peptide showed multiple sets of peaks of weak intensity, indicative of multiple conformations. On addition of excess drug, the total intensity increased and only one set of peaks per subunit was observed ( Fig.…”
Section: M2-s31n Inhibitormentioning
confidence: 98%
“…It predominated in 98-100% of the transmissible amantadineresistant H1N1, H5N1, and H3N2 strains isolated from humans, birds, and swine in the past decade. V27A and L26F are less frequent mutations (10,11,15). Extensive studies of point mutations to the pore-lining residues of M2 have been conducted to understand the paucity of natural variants (16,17).…”
Section: M2-s31n Inhibitormentioning
confidence: 99%
“…11,50-60 V27A and L26F are less frequent and generally have been found in nonpandemic amantadine-resistant H1N1. 48,61,62 Extensive studies of point mutations to the pore-lining residues of M2 have been carried out to probe the conductance mechanism and to identify additional sites that might impart amantadine-resistance.…”
Section: Natural and Artificial Sequence Variants Of M2mentioning
confidence: 99%